A cut-off in the TeV gamma-ray spectrum of the SNR Cassiopeia A - Ahnen, M. L.; Ansoldi, S.; Arcaro, C.; Babić, A.; Bangale, P.; Barres de Almeida, U.; Becerra González, J.; Bednarek, W.; Bernardini, E.; Berti, A.; Biasuzzi, B.; Biland, A.; et al. (Monthly notices of the Royal Astronomical Society, 2017)
Abstract It is widely believed that the bulk of the Galactic cosmic rays is accelerated in supernova remnants (SNRs). However, no observational evidence of the presence of particles of PeV energies in SNRs has yet been found. The young historical SNR Cassiopeia A (Cas A) appears as one of the best candidates to study acceleration processes. Between 2014 December and 2016 October, we observed Cas A with the MAGIC telescopes, accumulating 158 h of good quality data. We derived the spectrum of the source from 100 GeV to 10 TeV. We also analysed ∼8 yr of Fermi-LAT to obtain the spectral shape between 60 MeV and 500 GeV. The spectra measured by the LAT and MAGIC telescopes are compatible within the errors and show a clear turn-off (4.6σ) at the highest energies, which can be described with an exponential cut-off at $E_c = 3.5(^{+1.6}_{-1.0})_{{\rm stat}} (^{+0.8}_{-0.9})_{{\rm sys}}$ TeV. The gamma-ray emission from 60 MeV to 10 TeV can be attributed to a population of high-energy protons with a spectral index of ∼2.2 and an energy cut-off at ∼10 TeV. This result indicates that Cas A is not contributing to the high energy (∼PeV) cosmic ray sea in a significant manner at the present moment. A one-zone leptonic model fails to reproduce by itself the multiwavelength spectral energy distribution. Besides, if a non-negligible fraction of the flux seen by MAGIC is produced by leptons, the radiation should be emitted in a region with a low magnetic field (B⪅180 μG) like in the reverse shock.